Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2020)
The COVID-19 pandemic will exacerbate Spain's already large inclusion gap. Responding in the recovery with policies that support social objectives should be a key priority and calls for several structural changes. This paper summarizes some of the main drivers behind the social dispersion, which pre-dates the COVID-19 crisis, and policy options. The focus is on how to address the fragmented labor market, tackle pressures on rental-housing affordability, and lower the gender pay gap.1, 2.